PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI KEPRIBADIAN GURU PAI TERHADAP MOTIVASI BELAJAR SISWA SMP DI PEKANBARU - Muhammad Tomi; Risnawati; M. Fikri Hamdani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study aims to analyse the influence of teachers' pedagogical and personal competencies on the learning interest of junior high school students in Pekanbaru City. The study uses a quantitative approach with a survey method. There were 35 respondents in this study, selected using non-probability sampling techniques. Data were collected through a structured questionnaire with a five-point Likert scale that had been tested for validity and reliability. Data analysis was performed using SPSS software version 22 through several stages, including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination test. The results showed that, partially, teachers' pedagogical competence did not have a significant effect on students' interest in learning, while teachers' personal competence had a positive and significant effect on students' interest in learning. However, simultaneously, teachers' pedagogical competence and personal competence had a significant effect on students' interest in learning with a coefficient of determination of 0.496. This indicates that 49.6% of the variation in student learning interest can be explained by these two variables, while the rest is influenced by other factors outside the scope of this study.